Design and static analysis of improved grout joint of offshore monopile foundation. (3rd October 2017) - Lin, Yu-Hung; Huang, Hsin-Haou
Abstract : A wind turbine monopile usually consists of a "grout joint" that connects the pile with the sleeve and supports the wind turbine. The pile is misaligned frequently when driven into the seabed. The grout corrects the alignment of the sleeve and pile when the sleeve is installed. Nevertheless, the destruction of the concrete remains critical. This article focuses on the damage behaviour of the grout joints and proposes concepts for strengthening joints. The failure location and the maximum stress determined from a static numerical analysis are first discussed. To strengthen the traditional grout joint, two modified joints were designed, constructed, and compared with the traditional joint. Both numerical and experimental three-point bending tests of a small-scale monopile foundation were performed. Crack opening distances at the joint location of the specimens and the ultimate forces of the tests were measured and compared. The proposed modified grout joint demonstrates improved static load-carrying capability and lower stress in grout materials.